Pakistan : An Evaluation of the World Bank's Assistance - Independent Evaluation Group (Washington, DC: World Bank, 2012)
This book analyzes the objectives and content of the World Bank's assistance program during the period 1994-2003, the economic and social development outcomes in Pakistan, and the contributions of the Bank to development outcomes.